2011
DOI: 10.1088/0957-4484/22/47/475201
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of surface metal nanoparticles and their induced surface plasmon coupling with subsurface InGaN/GaN quantum wells

Abstract: Based on the fabrication of Ag nanoparticles (NPs) with controlled geometry and surface density on an InGaN/GaN quantum well (QW) epitaxial structure, which contains indium-rich nano-clusters for producing localized states and free-carrier (delocalized) states in the QWs, and the characterization of their localized surface plasmon (LSP) coupling behavior with the carriers in the QWs, the interplay behavior of LSP coupling with carrier delocalization in the QWs is demonstrated. By using the polystyrene nanosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14] Such a nanophotonic approach has been applied to light emitting devices. [15][16][17][18][19][20][21][22]24,25 The rationale behind is that the transfer of energy from carriers in GaInN QW into localized optical plasmon supported by the metallic nanostructures will create an a afad@fotonik.dtu. additional light emission channel called plasmonic channel.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Such a nanophotonic approach has been applied to light emitting devices. [15][16][17][18][19][20][21][22]24,25 The rationale behind is that the transfer of energy from carriers in GaInN QW into localized optical plasmon supported by the metallic nanostructures will create an a afad@fotonik.dtu. additional light emission channel called plasmonic channel.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, the reduction of metal NP size leads to a weaker SP coupling effect. 7 The other approach for blue-shifting LSP resonance spectrum is to insert a thin dielectric interlayer (DI) between a metal NP and the LED top layer with the refractive index of the DI lower than that of the LED semiconductor ($2.4 in GaN).…”
mentioning
confidence: 99%
“…It is reported that SP coupling is particularly useful for increasing emission efficiency of a light-emitting material of inherently low IQE [34]. In other words, the PL enhancement factor of materials with low IQE is higher than that of material with high IQE.…”
Section: Discussionmentioning
confidence: 99%